The Relationship of EMR (Electronic Medical Record) Documentation Performance with Patient Satisfaction - Agus Agus; Tri Ratnaningsih; Windu Santoso (GLOBAL HEALTH SCIENCE GROUP, 2025)
Technological developments have an impact on developments in the world of health, especially information technology in hospitals. The use of EMR makes medical records more orderly and improves health services that are faster, more precise, valuable and accountable. User usage and satisfaction will influence individual impact. Methods: An analysis of the relationship between EMR documentation and nurse satisfaction is needed. This study used a cross-sectional, The sampling technique in this research used purposive sampling correlational design with a sample of 80 patient at RSUD Dr. Soetomo. Research data was collected through questionnaires from the EMR documentation performance variables and nurse satisfaction. The results of the validity test of the EMR Documentation Performance instrument obtained a Parson correlation value in the range 0.590-0.926 > r table 0.514 and the results of the reliability test in this research showed a Cronbach's Alpha value of 0.966 so it is reliable. results of the validity and reliability of the patient satisfaction instrument Cronbach α reliability coefficient was high, ranging from 0.900 to 0.940. Research data was processed using the Spearmen rho test with a p value <0.05. Results: The results of the study showed that EMR documentation performance was related to patient satisfaction (0.009). Discussion: Good electronic medical record documentation performance can increase patient satisfaction.